O stopniach naukowych w Polsce Ludowej. Część 1. Niższe stopnie naukowe - Wojtczak, Krystyna (Studia Prawa Publicznego, 2019)
In the period researched in this article (1947–1990) the principles of awarding academic degrees were far from stable (or uniform). What is more, difference between individual degrees were of multiple character. In the initial years shortly after the Polish People’s Republic was formed, a lower academic degree was award ed to every higher school graduate. From 1951on this term referred to degrees awarded to science candidates, and as of 1958 to a degree of a doctor. Secondly, the requirements needed to be satisﬁed in order to qualify for individual degrees differed and were changing. Thirdly, on and off there were instances where ex emptions were made from the generally binding principles governing awarding of academic degrees, especially in the case of a science candidate and a doctor. Those exemptions, or exceptional treatment, was justiﬁed by a reference to an exceptional case. Fourthly, lower academic degrees could not always be obtained in every discipline, and the list of the discipline that qualiﬁed candidates for a degree was neither closed nor stable. Fifthly, the rights granted to scientiﬁc councils of institutions of higher education, and later to scientiﬁc councils of units operating within the Polish Academy of Sciences as well, were also changing, mostly to meet the conditions and requirements which those unites were obliged to fulﬁl. Sixthly, depending on the role and position of other bodies or organs involved in the process (the minister competent for schools of higher education, the Main Council of Higher Education, or the Central Qualiﬁcations Committee) their say and role was also changing. For the sake of a certain simpliﬁcation, it may be stated that solutions adopted as a result of the reforms of 1947 and 1951were comparable, while those implemented in subsequent years, particularly by acts on higher education of 1958, 1982 and 1985 and the act of 1965 on academic degrees and scientiﬁc titles as later amended, differed considerably from earlier solutions. The assessment, from a legal point of view, of the conditions of awarding lower academic degrees in the period researched would, however, have been incom- plete if the organisation of doctoral studies as well as the manner of their delivery leading to the preparation and submission of a doctoral dissertation by a degree candidate, had been examined as well. This issue will be the subject of the second part of this article.